MANAJEMEN KARIR: PERMASALAHAN MOBILITAS DAN PENGEMBANGAN KARIR INDIVIDU DALAM ORGANISASI - Theresia Diah Widiastuti (KINERJA, 2004)
This paper explores in depth some problems and issues related to individual careermobility at workplace and the role of organization in employee career development activities at work place. The exploration will be developed further by making advanced analysis on career management, especially the importance of career planning and development and also some obstacles for career mobility seen from an individual and organizational perspective. This paper also identifies some factors that facilitate individual career mobility process and a number of career development intervention activities in an organization.Keywords: career mobility, career management, career development intervention